Student Learning Motivation of Management Study Program in Improving English Speaking Skill - Rianita, Ni Made (Jurnal Pedagogi dan Pembelajaran, 2023)
Even though they have studied it from elementary school to high school, English is one of the subjects studied by students. However, their speaking ability is quite fluent. This research analyzes the Management Study Program students' learning motivation to improve their English speaking skills. This type of research is qualitative. The sample in this research was 87 first-semester students of the Management Study Program. The data collection technique uses primary data in the form of a questionnaire. The data analysis used is descriptive qualitative analysis. The results of this research show that the learning motivation of management study program students towards improving speaking skills is very high. Indicators showing that students have high motivation with frequency and persistence in completing assignments are almost 100% intrinsic motivation. Apart from that, students also have extrinsic motivation, which is shown by a sense of enjoyment in the learning environment and good achievement for their efforts in mastering speaking skills; students desire to master speaking skills better so that they can later be used in looking for work.